2018
DOI: 10.1159/000491551
|View full text |Cite
|
Sign up to set email alerts
|

Renal Hypoxia: An Important Prognostic Marker in Patients with Chronic Kidney Disease

Abstract: Background: Blood oxygen level-dependent (BOLD)-MRI is a novel and noninvasive tool that can assess renal oxygenation. The R2* value is a parameter of tissue deoxyhemoglobin concentration detected by BOLD-MRI. The purpose of the current study was to determine the relationships between renal R2* values and clinical parameters and to determine whether renal R2* values were associated with the risk for progression of chronic kidney disease (CKD). Methods: Sixty patients with CKD were enrolled in this prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 24 publications
6
23
1
Order By: Relevance
“…It is not yet clear if such modest change is due to the inherently lower sensitivity of BOLD MRI in evaluating cortical oxygenation [31] or whether the kidney compensates for the lower perfusion and maintains the oxygenation status. Unlike previous studies [26,27] reporting a significant association of cortical R2* with eGFR and eGFR_slope, we did not observe similar associations. We suspect this may be partly related to the moderate CKD in our study, limited range of eGFR values and the smaller number of subjects.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…It is not yet clear if such modest change is due to the inherently lower sensitivity of BOLD MRI in evaluating cortical oxygenation [31] or whether the kidney compensates for the lower perfusion and maintains the oxygenation status. Unlike previous studies [26,27] reporting a significant association of cortical R2* with eGFR and eGFR_slope, we did not observe similar associations. We suspect this may be partly related to the moderate CKD in our study, limited range of eGFR values and the smaller number of subjects.…”
Section: Discussioncontrasting
confidence: 99%
“…Only R2*_MC ratio showed significant differences between the CKD and control groups. The modest increase in cortical R2* is consistent with prior studies [26,27]. It is not yet clear if such modest change is due to the inherently lower sensitivity of BOLD MRI in evaluating cortical oxygenation [31] or whether the kidney compensates for the lower perfusion and maintains the oxygenation status.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Chronic hypoxia induces tubulotinterstitial fibrosis, which in turn could decrease the GFR [ 54 ]. In this regard, cortical hypoxia predicts a progressive decrease in renal function in patients with chronic kidney disease [ 55 , 56 ]. In contrast, SGLT2 inhibitors induced hypoxia in the outer stripe of the outer medulla (OSOM), but not in the cortex.…”
Section: Discussionmentioning
confidence: 99%
“…76 Moreover, various studies showed that cortical oxygenation independently predicts the progression of CKD by annual estimated glomerular filtration rate (eGFR) loss. [76][77][78] In addition, BOLD-MRI measurement has been combined with arterial spin labeling to quantify renal perfusion in patients with diabetes and stage 3 CKD. 79 The results indicated that cortical oxygenation in patients with mild to moderate CKD was reduced, although the measurement did not reach statistical significance.…”
Section: Renal Hypoxia and Dkd-evidence From Human Studiesmentioning
confidence: 99%